2014
DOI: 10.1073/pnas.1407018111
|View full text |Cite
|
Sign up to set email alerts
|

Protons are a neurotransmitter that regulates synaptic plasticity in the lateral amygdala

Abstract: Stimulating presynaptic terminals can increase the proton concentration in synapses. Potential receptors for protons are acidsensing ion channels (ASICs), Na + -and Ca 2+ -permeable channels that are activated by extracellular acidosis. Those observations suggest that protons might be a neurotransmitter. We found that presynaptic stimulation transiently reduced extracellular pH in the amygdala. The protons activated ASICs in lateral amygdala pyramidal neurons, generating excitatory postsynaptic currents. Moreo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

18
360
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 244 publications
(380 citation statements)
references
References 51 publications
(67 reference statements)
18
360
1
1
Order By: Relevance
“…There, synapses host an NGIC compliment kinetically suited to their input patterns (14) but are also capable of dynamically shifting between the priorities of integration and precision (8). Unsurprisingly then, influencing the deactivation kinetics of specific NGIC subtypes using allosteric modulators is a promising therapeutic objective (15-17).Acid-sensing ion channels (ASICs) have recently been shown to act as NGICs (18,19). In both the lateral amygdala (18) and the nucleus accumbens (19), the brief acidification of the synaptic cleft accompanying neurotransmission can activate postsynaptic ASICs that contribute to EPSCs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There, synapses host an NGIC compliment kinetically suited to their input patterns (14) but are also capable of dynamically shifting between the priorities of integration and precision (8). Unsurprisingly then, influencing the deactivation kinetics of specific NGIC subtypes using allosteric modulators is a promising therapeutic objective (15-17).Acid-sensing ion channels (ASICs) have recently been shown to act as NGICs (18,19). In both the lateral amygdala (18) and the nucleus accumbens (19), the brief acidification of the synaptic cleft accompanying neurotransmission can activate postsynaptic ASICs that contribute to EPSCs.…”
mentioning
confidence: 99%
“…A pH drop of 0.2-0.6 pH units or greater can accompany single-release events, but the synaptic cleft pH may not return directly back to physiological pH (21-25). Rather, following brief stimulations, synaptic cleft pH "overshoots" the physiological range by 0.2 pH units or more and remains alkaline for several tens or hundreds of milliseconds (18,(26)(27)(28). Cleft pH can also remain persistently acidic during prolonged bouts of activity, during stimulation, or during a variety of pathological conditions such as spreading depression or epileptic activity (27,29,30).…”
mentioning
confidence: 99%
“…The idea that protons can function as a neurotransmitter has existed for some time [35][36][37], however the precise role of ASICs in synaptic transmission and neuroplasticity remains still elusive [16,[37][38][39]. In fact, it has been suggested that ASIC1a may contribute to certain forms of synaptic plasticity in the hippocampus, although results are controversial [8,17,18].…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that ASICs are required for long-term potentiation (LTP) at cortico-basal lateral amygdala synapses, and are critical for associative fear learning and memory [16]. On the other hand, the role of ASICs in the hippocampus is still not clear [8,13,17,18] and may vary depending on the experimental conditions used.…”
mentioning
confidence: 99%
“…ASICs are mainly neuronal channels, which are activated by a sudden increase in the extracellular proton concentration (4). They are involved in the sensation of pain and mechanical stimuli, synaptic transmission, and various cognitive processes (5)(6)(7)(8)(9)(10)(11)(12). ENaC is mainly involved in the absorption of Na ϩ in a variety of tissues.…”
mentioning
confidence: 99%